Multiscenario-Based Train Headway Analysis under Virtual Coupling System - Jinyi Pan; Qiyuan Peng; Shuguang Zhan; Jiaqi Bai (Journal of Advanced Transportation)
Chinese high-speed railway has implemented large-scale network operation with an urgent need for capacity improvement. The concept of virtual coupling seems to be a promising solution that provides a new operational scenario for high-speed railway, where trains are formed into a cooperative convoy and run synchronously with small train headways. The train-following principles under the virtual coupling signalling are quite different from those under conventional train control systems. Therefore, train headway analysis for different operational scenarios should be carried out to ensure railway safety and evaluate capacity benefits brought by virtual coupling. This paper proposes a potential virtual coupling architecture with reference to ETCS/ERTMS specifications. We compare blocking time models under different train control systems, and eight typical train-following scenarios are investigated for virtual coupling, including train arrival and departure cases. A detailed multiscenario-based train headway analysis is provided based on the microscopic infrastructure of the station and technological characteristics of virtual coupling. All computational outcomes are based on the train dynamic motion model. A comparative analysis of train headways under virtual coupling and CTCS-3 is provided in the case study. Results show that train headways can be substantially reduced under virtual coupling and are related to the station infrastructure layout.